EXPRESSION OF NATIONAL AND CULTURAL VIEWS IN UZBEK FOLK TALES (American Journal of Research in Humanities and Social Sciences, 2024)
This article, using the example of Uzbek folk tales, shows that the analysis of the lexical-semantic and linguocultural aspects of the language of folk tales, the worldview, ideas, attitude of proverbs to reality, their unique vision, perception, understanding and explanatory style, is of great importance.